MOMENTUM: MetamOrphic malware exploration techniques using MSA signatures - Vinod, P.; Laxmi, V.; Gaur, M. S.; Chauhan, G. (2012 International Conference on Innovations in Information Technology, 2012)
Modern malware that are metamorphic or polymorphic in nature mutate their code by employing code obfuscation and encryption methods to thwart detection. Thus, conventional signature based scanners fail to detect these malware. In order to address the problems of detecting known variants of metamorphic malware, we propose a method using bioinformatics techniques effectively used for Protein and DNA matching. Instead of using exact signature matching methods, more sophisticated signature(s) are extracted using multiple sequence alignment (MSA). The results show that the proposed method is capable of identifying malware variants with minimum false alarms and misses. Also, the detection rate achieved with our proposed method is better compared to commercial antivirus products used in the study.